Occupying Power : Sex Workers and Servicemen in Postwar Japan. - Kovner, Sarah (Studies of the Weatherhead East Asian Institute, Columbia University., 2012)
The arrival of hundreds of thousands of Allied troops struck Japan like an earthquake, altering both the built environment and the country's psychological landscape. Made especially visible at the time were panpan--streetwalkers--desired by foreign servicemen. Though sex workers became symbols of Japan's diminished status, by earning scarce dollars they helped jumpstart economic recovery. But sex workers who catered to servicemen were a frequent target. They were blamed for increases in venereal disease and for diluting the Japanese race by producing mixed-race offspring. In 1956, newly empowere.